Vitamin A absorption determined in rats using a plasma isotope ratio method - Green, Michael; Green, Joanne Balmer (American Society for Nutrition, 2020)
Background Better methods are needed for determining vitamin A absorption efficiency. Objective Our objective was to measure vitamin A absorption in rats by adapting a plasma isotope ratio method previously used to determine cholesterol absorption. Methods Male Sprague-Dawley rats [n = 14; 340 ± 16 g (mean ± SD)] received an oral tracer dose of [3H]retinyl acetate in oil plus an intravenous dose of [14C]vitamin A–labeled lymph prepared in a donor rat that had received [14C]retinyl acetate intraduodenally. Blood samples were collected on days 1, 2, 3, 6, 9, and 12, and plasma was analyzed for 3H and 14C; vitamin A absorption was calculated for each sample as (fraction of oral dose/fraction of intravenous dose) × 100. Radioactivity was also measured in feces and urine collected as pools on days 3, 6, 9, and 12 and in liver and remaining carcass on day 12. Results Vitamin A absorption calculated as the plasma isotope ratio was >100% on day 1, 78% ± 5% on day 6, 76% ± 5% on day 9, and 74% ± 5% on day 12; fitting the data to an exponential function plus a constant predicted an absorption of 75% by day 14. Recovery of the oral dose in feces (day 0 to day 6) was low (6.2% ± 0.84%, n = 10) and the mean isotope ratio in day 9–12 urine pool was lower than that in plasma. Conclusions The plasma isotope ratio holds promise for estimating vitamin A absorption, but additional work is needed to determine how long studies need to be and if the doses should be administered simultaneously. For application of this method in humans, artificial chylomicrons labeled with a stable isotope of retinyl acetate could be used for the intravenous dose, with a different isotope required for the oral dose.